If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = -44 + -10x Reorder the terms: 12 + 5x = -44 + -10x Solving 12 + 5x = -44 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 12 + 5x + 10x = -44 + -10x + 10x Combine like terms: 5x + 10x = 15x 12 + 15x = -44 + -10x + 10x Combine like terms: -10x + 10x = 0 12 + 15x = -44 + 0 12 + 15x = -44 Add '-12' to each side of the equation. 12 + -12 + 15x = -44 + -12 Combine like terms: 12 + -12 = 0 0 + 15x = -44 + -12 15x = -44 + -12 Combine like terms: -44 + -12 = -56 15x = -56 Divide each side by '15'. x = -3.733333333 Simplifying x = -3.733333333
| 105-4x=2x-21 | | 9x+2=7x-12 | | -35-5x=13-10x | | c/2=9 | | X=3200*.80 | | 8.4=128 | | x+2-6x=x-9 | | 3-0.3k=3 | | -x+9=30 | | ((5y-2)/8)=(2+(y/4)) | | x+2-6x=x-(9-5x) | | 2z+4z=5z-4 | | 216x^6+1/64 | | 6t-t-4=4t-5 | | 6x+x-8=6x+3 | | (x-1)(x-1)(x-1)=y | | 2g(g+7)= | | H(4-5h)= | | x^3-7x=0 | | 6/z-4.4=0.4 | | x^1/2/x^3/4 | | 6/4.8 | | g+a+y=g*a*y | | 1g+1a+1y=gay | | (4x^2+7x)(25x^2-5x-2)=0 | | 6e-14=30-5e | | 870.1166666666667x=569.20x+69679.56666666667 | | 870.1166666666667x=569.20x+165684.6333333333 | | 870.1166666666667x=569.20x+67924.53333333333 | | 24/100 | | 5(7-8y)=-85 | | sin(x)=0.26 |